Understanding regression analysis an introductory guide - Schroeder, Larry D. (Quantitative applications in the social sciences ;, 1986)
Providing beginners with a background to the frequently-used technique of linear regression, this text provides a heuristic explanation of the procedures and terms used in regression analysis and has been written at the most elementary level.